Management of uterine fibroids in the patient pursuing assisted reproductive technologies. (July 2009) - Ezzati, Mohammad; Norian, John M; Segars, James H
Uterine leiomyomas are present in 30–70% of women of reproductive age. In addition to causing menstrual disorders and pain, uterine fibroids negatively affect fertility and pregnancy outcome for patients pursuing assisted reproduction. The two questions that have to be addressed are: which fibroids should be treated and how should they be treated? Submucosal fibroids are associated with a 70% reduction in delivery rate. Intramural fibroids had a lesser effect and reduced the delivery rate by approximately 30%. By contrast, studies have demonstrated that subserosal fibroids did not negatively impact fertility. Furthermore, both submucosal and intramural fibroids were associated with an increased risk of spontaneous miscarriage. Myomectomy is considered the treatment of choice to alleviate these detrimental effects. Further research is needed before alternative treatments can be recommended.